Immigrants and the labour force : policy, regulation, and impact - Pendakur, Ravi (McGill-Queen's University Press, 2000)
First, Canada's primary source for immigrants has shifted dramatically from the United Kingdom and Europe to countries outside Europe. Second there has been a remarkable transformation in the nature of work: Canada's economy has changed from relying on resource extraction to an emphasis on manufacturing, and presently is emerging as post-industrial and knowledge-based. Pendakur combines an analysis of parliamentary debates on immigration issues with an evaluation of the regulatory and policy changes that resulted from these discussions and an analysis of how the work of immigrants changed over a five-decade. He then provides both a political and quantitative analysis by looking at issues that affect not only immigrants but minorities born in Canada in order to assess the degree to which labour market discrimination exists and whether employment equity programs are needed.